Association between depression and health care expenditure in middle-aged and older patients with heart disease. - Shushu You; Xiang Gu; Jing Sui; Ziyu Xiang; Fan Gao (PLoS ONE)
Objective Patients with heart disease frequently experience a heightened incidence of depression, thereby affecting their overall medical expenditures. Nevertheless, earlier investigations have focused on the healthcare costs incurred by individual patients with heart disease or those with depression. The present study assessed the correlation between depression and the medical expenditures of patients with heart disease, highlighting the importance of mental health care for patients with with heart disease. Method Using data from Charles, we identified 2445 middle-aged and older patients with heart disease based on their completed medical expenditure-related questionnaires. The study further calculated the questionnaire data and used multiple linear regression analysis to control for demographic variables to evaluate the relationship between depressive symptoms and medical expenses. Results In our sample, the presence or absence of depressive symptoms exhibited statistically significant differences (p < 0.05) in the medical expenditures of patients. Approximately 50.27% of heart disease patients had depressive symptoms. Depression level, gender, education level, type of health insurance, consumption level, and number of other chronic diseases were significantly associated with higher medical expenditures. A positive correlation was found between depressive symptoms and medical expenses. Conclusion Heart disease patients exhibiting depressive symptoms incurred higher medical expenditures compared to their counterparts without depression. The findings of this study imply the need to augment mental health care services for older individuals with heart disease and to enhance collaborative care interventions within the context of heart disease.